Does the abstract thinking have a significant role in the relationship between extraversion and evoked brain potentials? - Tatalović Vorkapić, Sanja (Array, 2011)
Considering the significant number of inconsistent results regarding the relationship between extraversion and evoked potentials within the Eysencks’ arousal theory, a possible significant role of some other variables such as attention, task modality and difficulty, and intelligence level has been analyzed. The aim of this study was to analyze the relationship between extraversion and its electrophysiological correlates, taking into account the intellectual level of subjects. Forty-three female psychology students, within the age range 19-23 years, participated in the study. Extraversion was measured by EPQ-R and abstract thinking by ATT. The evoked brain potentials (N1, P2, N2, P3, & SW) were elicited by a standard visual oddball paradigm, in two measurement trials for each subject, using two occipital and two parietal electrodes. Correlation analyses of extraversion and evoked potentials partialized for abstract thinking have shown that the intellectual level of subjects represented a significant part of the extraversion-evoked potentials relationship, especially in the SW-latency parameter. Overall, the findings implied the great importance of analyzing individual differences in electro-cortical activity using the measures of both personality and intelligence, as both of them could play a significant and complex role in subjects’ cortical arousal.